Hubungan Indeks Massa Tubuh dan Asupan Makanan dengan Siklus Menstruasi pada Remaja Akhir - Neysa Khanifatun Nabila; Hernandia Distinarista; Apriliani Yulianti Wuriningsih; Sri Wahyuni (Journal of Medical Practice and Research, 2025)
This study examined the relationship between body mass index and dietary intake with menstrual cycle regularity among late adolescents. A cross-sectional analytical design was conducted among 135 female students selected through stratified random sampling. Body mass index was assessed using anthropometric measurements, while dietary intake and menstrual cycle characteristics were collected through validated questionnaires. Data were analyzed using univariate analysis and Spearman rank correlation tests. The findings revealed a significant association between body mass index and menstrual cycle regularity, indicating that adolescents with non-normal body mass index were more likely to experience menstrual irregularities. In addition, dietary intake showed a significant positive correlation with menstrual cycle patterns, suggesting that unhealthy eating behaviors contribute to cycle disturbances. These results highlight that nutritional status and dietary quality are interrelated factors influencing hormonal balance and reproductive function during late adolescence. The study underscores the importance of maintaining a normal body mass index and adopting balanced dietary habits to support menstrual health. The findings provide empirical evidence to inform health promotion programs focusing on nutrition and reproductive health among adolescent populations.